EDUCATIONAL PROBLEMS IN THE CONTEXT OF THE OPEN INFORMATIONAL ENVIRONMENT - Gennady A. Klekovkin (Образование и наука)
The research is aimed at investigating the negative consequences of IT implementation in education related to the open informational environment. The author continues to explore the issue emphasized by V.A. Testov in ≪Mathematical Education in the Network Environment≫ (№ 2, 2013).Methods: The methods involve the analysis of modern trends and techniques of IT implementation in education.Results: The research outcomes include the examples of possible adverse trends and phenomena resulting from the use of hypertext, multimedia and network technologies, as well as different informational instrumental environments that enable the user to automatically control the cognitive operations. Scientific novelty: The author singles out and summarizes the problems of fostering the critical thinking and correlation between the systematic knowledge, acquired in educational process, and fragmentary one, received from various alternative information sources.Practical significance: The research findings can help practicing teachers minimize the negative phenomena, related to implementation of new electronic educational technologies, and provide a starting point for further research in the given field.